Genomics and Molecular Phylogenetics Tree Analysis of Actinopolyspora Iraqiensis - Salih, Talal Sabhan; Shafeek, Raghad Riyadh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Actinopolyspora iraqiensis IQ-H1 is a novel strain of actinobacteria isolated from extremely halophilic soil samples in Iraq. The whole-genome sequence of this strain is deposited in the National Center for Biotechnology Information (NCBI) GenBank under the accession number NZ_AICW01000000. In this study, the genome features and the molecular phylogenetic tree of Act. iraqiensis IQ-H1are analyzed. The RAST tool was used for genome annotation. The genomic features were elucidated using QUAST tool. The circular genome map, and the core and pan-genome map of Act. iraqiensis IQ-H1 was generated using CGView and the GView tools respectively. The JSpeciesWS server was used for the tetranucleotide signature analysis and the REALPHY server was utilized for the construction of the whole genome sequence based phylogenetic tree. The genome size of the strain was around 4.0 Mpb and the number of contigs was 110 with a GC content of 70.46%. The core genome of Act. iraqiensis IQ-H1 was estimated to be 2.2 Mpb. Based on z-scores of the tetranucleotide signature analysis, Act. halophila DSM 43834, Act. mortivallis DSM 44261 and Act. saharensis DSM 45459 were the most relative strains to Act. iraqiensis IQ-H1with z-scores 0.99784, 0.98943 and 0.99789 respectively. Based on the phylogenetic tree constructed from the whole genome sequences, Act. iraqiensis IQ-H1 was the most closely related to Act. saharensis DSM 45459, Act. halophila DSM 43834 and Act. mortivallis DSM 44261. The results suggest that the web-based bioinformatics tools such as QUAST, CGView, GView, JSpeciesWS and REALPHY can be utilized for the analysis of the genomic features of Act. iraqiensis IQ-H1 and other species of the genus Actinopolyspora.